On the role of consumer expectations in markets with network effects - Irina Suleymanova; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2010)
We analyze the role of consumer expectations in a Hotelling model of price competition when products exhibit network effects. Expectations can be strong (stubborn), weak (price-sensitive) or partially stubborn (a mix of weak and strong). As a rule, the price-sensitivity of demand declines when expectations are more stubborn. An increase of stubbornness i) reduces competition, ii) increases (decreases) the parameter region with a unique duopoly equilibrium (multiple equilibria), iii) reduces the conflict between consumer and social preferences for de facto standardization, and iv) reduces the misalignment between consumer and social preferences for compatibility.
Keywords: D43; D84; L13; 330; Network Effects; Expectations; Duopoly; Compatibility; Welfare; Preiswettbewerb; Network Externalities; Hotelling Modell; Konsumtheorie; Erwartungstheorie; Duopol; Wohlfahrtseffekt; Theorie